Exploring Diet Quality, Food Insecurity, and Health Status among Utah Residents - Palak Gupta; Lendel Narine (Journal of Human Sciences and Extension)
A lower-quality diet is a significant contributor to preventable mortality worldwide. This study investigated the intricate relationships between diet quality, food insecurity, and health status among residents in Utah. Using a cross-sectional survey design with a sample size of 1,522 participants, data were collected through an online survey focusing on household characteristics, diet quality, health status, and food security. The primary exposure, household food insecurity, was assessed using a validated 6-item scale, while diet quality was measured through a modified Rapid Eating Assessment for Participants– Shortened Version (REAP-S). The findings revealed an association between very low food security and poor diet quality, particularly for individuals with reduced fruit and vegetable intake. Our study also revealed associations between poor diet quality, barriers to accessing healthy foods, and poor health status. Education emerges as a crucial determinant, showing higher educational attainment positively linked to improved diet quality. The findings underscore the need for targeted interventions, community-based educational programs, policy advocacy, and collaborative approaches to address these complex and interconnected issues. The present study contributes valuable insights to public health initiatives aiming to enhance overall health outcomes by addressing the multifaceted challenges of poor diet quality, food insecurity, and barriers to healthy eating.